2013
DOI: 10.3390/ijms140612273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcriptional Regulation of the Human miR-17-92 Cluster; Evidence for Involvement of Pim-1

Abstract: The human polycistronic miRNA cluster miR-17-92 is frequently overexpressed in hematopoietic malignancies and cancers. Its transcription is in part controlled by an E2F-regulated host gene promoter. An intronic A/T-rich region directly upstream of the miRNA coding region also contributes to cluster expression. Our deletion analysis of the A/T-rich region revealed a strong dependence on c-Myc binding to the functional E3 site. Yet, constructs lacking the 5′-proximal ~1.3 kb or 3′-distal ~0.1 kb of the 1.5 kb A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…1B-D); as was miR-17-5p (P ¼ 0.049), which is cotranscribed with miR-19 in cells. 24 However, due to high sequence homology, miR-17-5p could not be distinguished accurately from miR-106a in the array (Fig. 1C, D).…”
Section: Results Mirna Serum Arraymentioning
confidence: 91%
“…1B-D); as was miR-17-5p (P ¼ 0.049), which is cotranscribed with miR-19 in cells. 24 However, due to high sequence homology, miR-17-5p could not be distinguished accurately from miR-106a in the array (Fig. 1C, D).…”
Section: Results Mirna Serum Arraymentioning
confidence: 91%
“…These growth factors activate key transcription factors which, in turn, lead to upregulation of miRNAs. The VEGF-, EGF- and PDGF-responsive transcription factors, including E2F3 and Pim-1, have been reported to positively regulate miR17-92 expression [2628]. The promoter regions of miR17-92 genes contain an E2F binding site (TTTSSCGC), and binding of E2F3 to these promoter regions activates their expression and promotes cell proliferation [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The promoter regions of miR17-92 genes contain an E2F binding site (TTTSSCGC), and binding of E2F3 to these promoter regions activates their expression and promotes cell proliferation [27, 28]. Thomas et al [26] reported that the proto-oncogene Pim-1 is part of the network that regulates transcription of the miR-17-92 cluster. Therefore, the transcriptional program activated by serum to promote proliferation may at the same time inhibit apoptosis through a miR-92a-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs are overexpressed in BCR/ABL1-positive ALL (27,33) (Table I). BCR/ABL has been shown to upregulate Pim-1 (34,35), E2F3 (36) and c-Myc (35) who regulate the transcriptional expression of miR-17-92 clusters. Recently, it was reported that BIM, a proapoptotic member, is a direct target of miR-17-92 clusters (37).…”
Section: Mirna Expression and Oncoproteins In Acute Lympho Blastic Lementioning
confidence: 99%